2017
DOI: 10.15625/0866-7187/39/3/10268
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal features of oceanographic characteristics in upwelling Vietnam waters under impact of El Niño events

Abstract: The summer upwelling that occurs in coastal waters of South Central Vietnam is one of the major hydrographic features in the East Sea. A weakening of the upwelling after major El Niño events was observed in the literature for previous El Niño events and was verified here from the analysis of new satellite image data sets of sea surface temperature (SST) and surface wind. The analysis of empirical orthogonal function (EOF) from of monthly SST as well as of temporal and spatial variations of SST and wind force a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In contrast, the longshore current has a South-to-North direction during dominant Southwest monsoons, which is one of the causes of creating an anticyclonic gyre off the coast from Ninh Thuan to Binh Thuan, Vietnam (11 o N-13 o N). This anticyclonic gyre is the leading cause of the upwelling phenomenon in the South-Central Sea of Vietnam [28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the longshore current has a South-to-North direction during dominant Southwest monsoons, which is one of the causes of creating an anticyclonic gyre off the coast from Ninh Thuan to Binh Thuan, Vietnam (11 o N-13 o N). This anticyclonic gyre is the leading cause of the upwelling phenomenon in the South-Central Sea of Vietnam [28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…The studies on the variability of the upwelling system in the South-Central Vietnam waters under ENSO events and its impact on hydrographic conditions of the Ninh Thuan-Binh Thuan waters [18] have shown that the La Niña events can degrade and eliminate the upwelling phenomenon. The study of abnormal features of oceanographic characteristics in upwelling Vietnam waters under the influence of El Niño events [19] has partly clarified the impact of the El-Niño phenomenon on the occurrence time and position of the center region of the Vietnam upwelling waters. Based on 28 years of reanalysis data, the analyzed results showed that in the El Niño years, autumn rainfall in Central Vietnam is reduced by about 10 to 30% [20].…”
Section: Introductionmentioning
confidence: 99%